Sosialisasi Pengaruh Tindakan Bullying dan Penanganannya di SD Negeri 10 Manggar Baru Kota Balikpapan - Firman, Firman; Dwirakha, Yusuf; Qodir, Isma Hanafiah; Riansyah, Riansyah; Hidayat, Fahmi; Suhardi, Suhardi; Effendy, Nada Mulia Septyani; Tanadi, Tjan Stefany (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
This service aims to implement the socialisation programme on the influence of bullying and how to deal with it on students of Grade VI at SD Negeri 010 Manggar Baru. The socialisation is conducted in order to anticipate the occurrence of bullying against adolescents, especially the students of SDN 10 who are actually the future generations. This community service was conducted at SD Negeri 10 Manggar Baru, Balikpapan City with the subject of Grade VI students. The service educates the students about what bullying is and its effects. The impact of bullying is very influential on students' mental health, academic performance and social relationships. Efforts to anticipate bullying in schools are education about bullying , involvement of parents and community and consistent implementation of school rules. The stages of socialisation implementation are reporting and coordinating with the school, preparing materials, hearing the principal and class teacher, preparing the venue and media needed. Furthermore, the results of this activity provide the students with knowledge about the meaning, influence, impact and how to deal with it. In this way, the anticipation of the spread of bullying behaviour among school children can be dealt with at an early stage.